Karakteristik Pembelajaran Tematik Yang Ideal Pada Sekolah Dasar - Siti Rahimah Ikhsani; Arrum Tangawunisma; Atika Sholeha; Putra Divanka; Dede Indra Setiabudi (Student Scientific Creativity Journal, 2023)
Thematic learning in elementary schools has several special characteristics that distinguish it from other learning approaches. Children of school age / 6-12 years are called school age, because children have finished kindergarten as a real preparatory institution. It is called the ripe period for learning, because the child has tried to achieve something, but the activity of playing development is only aimed at getting pleasure when doing the activity itself. It is called a mature period for school, because children already want new abilities, which can be provided by schools (Nasution Noehi, 1993: 44). According to Banett, et al., the characteristics of elementary school age children are as follows. (1) They are naturally curious and interested in the world around them. (2) Enjoys playing and prefers to have fun. (3) Likes to organize himself to handle things, explore a situation and try new ventures. (4) usually thrilled and driven to excel because they do not like to experience dissatisfaction and reject failures. (5) Learn effectively when satisfied with the situation that occurs. (6) Learning by working, observing, taking initiative and teaching other children (Mulyani Sumantri & Nana Syaodih, 2000: 12).